(untitled) (Archive of Conferences, 2021)
Genghis Aytmatov peoples writer of Kyrgyzstan (1968). Academician of the Kyrgyz Academy of Sciences (1974). He graduated from the Kyrgyz Agricultural Institute (1953) 1956-58 years is a listener of the higher literature course of the Writers Union of Moscow.